Sliding adhesive contact of elastic solids with stochastic roughness. (April 2016) - Galanov, Boris A.; Valeeva, Irina K.
Abstract: The surface roughness and interfacial interaction are described by a thin Winkler–Fuss layer which covers the contacting solids and can resist to compressive and tensile stresses. The mechanical properties of this layer are determined by statistical theories of adhesion between nominally flat rough surfaces. The contact of the bodies with curved nominal surfaces and a priori unknown nominal contact regions is simulated by nonlinear boundary integral equations, whose solutions define and predict the deformation of the rough layer, the nominal contact stresses (normal and shear), the nominal contact regions, the adhesion force, the friction force and its nonlinear dependence on the normal force. The contribution of the adhesive forces in the total friction force is evaluated. The numerical results and their analysis for some problems are presented. The model can be applied to sliding contact problems for solids with arbitrary nominal geometry.